An Overview of the Effect of Hot Corrosion in Waste-to-Energy (WTE) Plant Environment - Singh, Harminder; Sidhu, T. S.; Kalsi, S. B. S. (Asian Journal of Engineering and Applied Technology, 2012)
The present study aims to study the hot corrosion behavior of the various alloys used in boiler tubes in the waste-to-energy plants. This study found that in the aggressive environment of waste to energy plants, there is failure of the boiler tubes due to hot corrosion and these plants are running at very less efficiency as compared to fossil fuel based power plants. It is also found that degradation problem in medical waste based plants is even more severe. The aggressive environment of these plants is mainly due to the presence of chlorine elements in the waste, used as fuel. In this study, a brief review of the performance of different alloys has been made in the environment of waste to energy plants.